Belajar Sebagai Jalan Menuju Kemerdekaan: Studi Analisis Konsep Pendidikan Ki Hajar Dewantara - Hanin Fathan Nurfina Istiqomah; Veni Sofia; Yelykha Henirayuza Nasution; Muh Irfan Ali; Mar’atun Sholiha; Salman Hasani (MAN 4 Kota Pekanbaru, 2025)
Learning, according to Ki Hajar Dewantara, is not merely an effort to acquire knowledge, but a continuous process of guiding human potential toward the realization of freedom and wholeness. This study aims to analyze Ki Hajar Dewantara’s educational concept, emphasizing the philosophical foundations of learning as a path to human liberation. Using a library research method, this paper explores the principles underlying Dewantara’s thought, including the principles of independence, natural law (kodrat alam), and culture, which serve as the basis for forming a free and responsible human being. The findings reveal that learning, in Dewantara’s view, functions as a moral and intellectual guide that leads individuals toward the highest form of happiness and harmony, becoming manusia merdeka, or liberated humans. This concept remains profoundly relevant in the context of modern education, particularly in the era of Society 5.0, where technological progress must be balanced with humanistic and ethical awareness. The study further provides a theoretical contribution by reaffirming the urgency of human-centered education and offers practical insights for redesigning 21st-century learning to cultivate independence, critical consciousness, and moral responsibility.